Strategies to improve research skills in a virtual learning context - Sánchez Trujillo, María de los Ángeles; Rodríguez Flores, Eduar Antonio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The objective of this research, developed in the context of virtual education, was to improve the investigative skills of university students. This qualitative study with an action-research design was based on an initial diagnosis, in which academic plagiarism was identified, as well as a medium or low-level self-perception regarding the research skills of the students. During the execution of the designed strategies, the techniques of focus group and documentary analysis of the student essays were applied. It was concluded the effectiveness of the strategies in improving basic skills, information search and analysis, and attitudinal skills.